Sharia Banks as A Pillar of Islamic Economic Transformation and Financial Stability Towards Equitable Prosperity - Ekawaty, Marlina (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The background of this study highlights the rapid growth of global and Southeast Asian Islamic finance, emphasizing the strategic role of Sharia banks in promoting equitable economic transformation. The aim of this research is to systematically review the literature on the role of Sharia banks as pillars of Islamic economic transformation and financial stability towards equitable prosperity. The research method employed a systematic journal review with inclusion criteria for studies published between 2015–2024, following PRISMA guidelines. A total of 15 eligible articles were analyzed to synthesize consistent patterns and findings. The results indicate that Sharia banks play a vital role in poverty alleviation, financial inclusion, real sector financing, and resilience to financial crises. Moreover, the integration of social and commercial orientations strengthens their contribution to sustainable growth. In conclusion, Sharia banks have the potential to serve as both pillars of financial stability and drivers of social justice in the global economy.